Dietary sodium intake and its relationship to adiposity in young black and white adults: The African‐PREDICT study. Issue 8 (1st July 2018) - Crouch, Simone H.; Ware, Lisa J.; Gafane‐Matemane, Lebo F.; Kruger, Herculina S.; Van Zyl, Tertia; Van der Westhuizen, Bianca; Schutte, Aletta E.
Abstract : Obesity and salt intake are both established factors contributing to cardiovascular disease development. Recently, studies found a controversial positive relationship between dietary salt and obesity. Therefore, the authors investigated whether obesity‐related measures are associated with 24‐hour urinary sodium in a healthy biethnic population. The study included 761 adults (20‐30 years) with complete 24‐hour urinary sodium, anthropometry, and bioelectrical impedance measurements. In single regression analyses all obesity‐related measures related positively with 24‐hour urinary sodium ( P ≤ .008). However, with multivariate adjustments for energy intake, accelerometery, age, sex, black and white ethnicity, and other covariates, only body surface area (BSA) remained independently associated with 24‐hour urinary sodium ( R 2 = 0.72, β = .05, P = .039). To conclude, we found a consistent and robust positive relationship between BSA and estimated salt intake – but not with traditional obesity measures such as body mass index (BMI). Further studies are needed to investigate body surface area and potentially, skin area, in salt handling.